2018
DOI: 10.36076/ppj.2017.1.e65
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Safety of Contra-Lateral Oblique View for Interlaminar Epidural Needle Placement

Abstract: Cord trauma is a risk with a cervical and thoracic interlaminar epidural approach to the epidural space. Intermittent lateral fluoroscopic imaging to detect needle depth is often cumbersome and may be difficult to interpret. In comparison, the contra-lateral oblique (CLO) fluoroscopic view is efficient and easy to interpret. However, the in vivo reliability and safety of this technique has not been formally investigated. The senior author collected fluoroscopic images on 278 consecutive patients undergoing an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The recognition that the lateral view may be suboptimal for needle tip visualization with no consistent radiological landmark defining the epidural space, particularly in the cervicothoracic region led to further supportive investigation of the CLO view as a viable alternative 13,14 . Additional investigations further validated that this view is efficient and reliable in visualizing the needle tip in relation to the epidural space at T1 with close inter‐observer agreement and little physician instruction 21 . A recent survey of interventional pain physicians found that for epidural access during SCS lead insertion, up to 90% used the lateral view, and 65% used the CLO view 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recognition that the lateral view may be suboptimal for needle tip visualization with no consistent radiological landmark defining the epidural space, particularly in the cervicothoracic region led to further supportive investigation of the CLO view as a viable alternative 13,14 . Additional investigations further validated that this view is efficient and reliable in visualizing the needle tip in relation to the epidural space at T1 with close inter‐observer agreement and little physician instruction 21 . A recent survey of interventional pain physicians found that for epidural access during SCS lead insertion, up to 90% used the lateral view, and 65% used the CLO view 22 .…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Additional investigations further validated that this view is efficient and reliable in visualizing the needle tip in relation to the epidural space at T1 with close inter-observer agreement and little physician instruction. 21 A recent survey of interventional pain physicians found that for epidural access during SCS lead insertion, up to 90% used the lateral view, and 65% used the CLO view. 22 However, a fluoroscopic view to determine needle tip depth, whether lateral or CLO was used by only 45%-60% of respondents during needle placement.…”
Section: Lateral Fluoroscopic View Onlymentioning
confidence: 99%
“…We did not use the lateral view during advancement to the inferior lamina because before the needle touches the lamina, only subcutaneous fat and muscles are located in the needle's path. The ligamentum flavum, to which we should pay more attention, exists on the inner side of lamina [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the CLO view is especially useful in upper thoracic and cervical access where the interlaminar window is narrow, the margin of error very low (small dorsal epidural space), and the lateral view is particularly suboptimal because of shoulder overlap. The contralateral oblique view has also been validated in other larger studies (15).…”
Section: Lateral and Contralateral Oblique View Use For Scs Lead Inse...mentioning
confidence: 95%